IJCM_136A: Prevalence Of Risk Factors For NCDs And Its Associated Factors in Rural Field Practice Area of RDJMMCH, Turki, Muzaffarpur, Bihar. - Singh Tulika; Priya Prachi; Kumar Madhu Rendra; Kumar Pawan; Kumar Arun (Wolters Kluwer Medknow Publications, 2024)
Background: Non-communicable diseases (NCDs) are diseases that are not transmissible directly from one person to another. NCDs mainly consists of cardio vascular diseases, diabetes, stroke etc. It accounts for 68% of global deaths. The prevalence rates in India is1.6% to 7.4% and 1% to 13.2% in rural and urban population respectively. Objective: To determine the prevalence and associated risk factors for NCDs in rural field practice areas of RDJMMCH, Turki, Muzaffarpur. Methodology: A cross-sectional study done among people above 30 years of age residing in study area from March to April, 2023. Data was collected using CBRA (community-based risk assessment) checklist for NCDs. Sample size of 157 was calculated assuming the prevalence of risk factor for NCDs being 30% with 95% confidence interval and absolute precision of 7.5%. Systematic random and simple random sampling was applied. Results: Mean age of participants was 47.9 years. Majority of them were females (56%) belonging to Hindu religion (98%). 41% were illiterate and major occupation practiced was farming (74%). Prevalence of risk factor for NCDs was 17.2%. On performing Chi-Square test smoking, alcohol, physical inactivity and family history of NCD’s were found to be significantly associated. Conclusion: As prevalence of risk factor for NCDs is 17.2%. Thus, it is the need of hour to have timely update about the disease and motivate them for healthy lifestyle.